PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP MINAT BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA DI KELAS IV SD NEGERI 10 TANJUNG LAGO - Desi Hari Wahyuni; Widya Handayani, Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' interest in learning mathematics is still low due to the implementation of conventional learning models. Lack of use of interactive learning media therefore this study aims to (1) determine the effect of using wordwall media on students' learning interest in learning mathematics in grade IV of STATE ELEMENTARY SCHOOL 10 Tanjung Lago. This study uses the Pre-experimental Design method with a research design of